Perjanjian Kerjasama PT. BRI Kantor Cabang Mataram Dengan Agen BRI Link Dalam Pencairan Bantuan Sosial PKH Di Kecamatan Gerung - Wawan Satriawan; Wiwiek Wahyuningsih (Fakultas Hukum Universitas Mataram, 2022)
This research aims to find out and explain cooperation agreement between BRI Bank and BRILINK Agent in distributing Social Security PKH and legal relationship, implementation procedure, and obstacles of cooperation agreement through BRILink Agent. The method of this research is normative-empirical legal research. The result of this research shows that legal relation between BRI Bank and BRIlink Agent is based on agency agreement that bound both parties. The implementation procedure of the cooperation agreement is conducted by contract, based on cooperation agreement procedure of disbursemant social security of PKH is executed by the BRILink Agent. There are several obstacles which are faced in cooperation agreement in disbursement social security PKH that consist of technical obstacles and many account number from PKH recipient community which is blocked.